Association of Age, Gender, and Body Mass Index with Coordination in Adults: A Cross-sectional Study - Firdosh Firozbhai Shekh; Harsha Ramrakhiyani; Pragna Landge (Journal of the Scientific Society)
Background: Coordination is the ability to execute smooth, accurate, controlled movement. The worldwide prevalence of developmental coordination disorder is 6%. Aging causes changes in the capacity to carry out fluid, precise, and controlled motor responses. The link between coordination and body mass index (BMI) was the opposite. Boys are typically more active than girls in their daily lives. The outcome measure is the Comprehensive Coordination Scale (CCS). Aim: The aim of this study was to study the relationship of age, gender, and BMI with coordination in adults. Materials and Methodology: 374 participants who met the inclusion criteria were recruited from various areas of Vadodara district. Then, use CCS which is composed of six components. Then applied all 6 components on each participant. The total score will be calculated. Then correlate these scores between the age, gender, and BMI of the participants and after that determine if any correlation between age, gender, and BMI with coordination of participants is present or not. Results: Data were calculated using standardized questionnaire. Analyses were performed with SPSS version 27.0, R version 4.2. Data normality was determined using Shapiro–Wilk test. Spearman’s rank correlation test was applied to find the correlation between age and BMI with coordination and point – Biserial correlation test was applied to find the correlation between gender and coordination. P <0.05 was considered statistically significant. Conclusion: The present study concluded that age has a positive correlation with coordination, gender has no correlation at all, and BMI has a negative correlation with coordination.